2017
DOI: 10.3847/2041-8213/aa91c9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-messenger Observations of a Binary Neutron Star Merger*

Abstract: On 2017 August 17 a binary neutron star coalescence candidate (later designated GW170817) with merger time 12:41:04 UTC was observed through gravitational waves by the Advanced LIGO and Advanced Virgo detectors. The Fermi Gamma-ray Burst Monitor independently detected a gamma-ray burst (GRB 170817A) with a time delay of ∼ 1.7 s … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
2,132
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 3,626 publications
(2,257 citation statements)
references
References 181 publications
51
2,132
0
10
Order By: Relevance
“…Rapid optical follow-up by our Dark Energy Camera (DECam) program (Flaugher et al 2015), starting just 11.4 hr after the GW trigger, led to the discovery of an associated optical counterpart in the nearby ( » d 39.5 Mpc; Freedman et al 2001) galaxy NGC 4993 (Allam et al 2017;Soares-Santos et al 2017). This optical source was independently discovered by several groups (Abbott et al 2017b), and first announced as SSS17a by Coulter et al (2017aCoulter et al ( , 2017b. The source has also been independently named DLT17ck Yang et al 2017) and AT2017gfo.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid optical follow-up by our Dark Energy Camera (DECam) program (Flaugher et al 2015), starting just 11.4 hr after the GW trigger, led to the discovery of an associated optical counterpart in the nearby ( » d 39.5 Mpc; Freedman et al 2001) galaxy NGC 4993 (Allam et al 2017;Soares-Santos et al 2017). This optical source was independently discovered by several groups (Abbott et al 2017b), and first announced as SSS17a by Coulter et al (2017aCoulter et al ( , 2017b. The source has also been independently named DLT17ck Yang et al 2017) and AT2017gfo.…”
Section: Introductionmentioning
confidence: 99%
“…We observe UHECR particles, and two scenarios are viable to explain them, with probably both realized in nature [52]: one is based on the relativistic jets and their shock waves in radio galaxies (e.g., [46]), and the other on Gamma Ray Bursts (GRBs) and their relativistic jets. Both sites of origin may involve mergers of black holes or neutron stars [51,53], or the ab initio formation of black holes. In a series of papers by Mannheim, Falcke and Markoff (e.g., [43,54,55]) it has been shown that at a distance of order 10 3.5 to 10 5 Schwarzschild radii from a central black hole a reconfinement shock system occurs, starting the routine jet flow (e.g., [56,57]).…”
Section: High-energy Neutrino Emission In Agnmentioning
confidence: 99%
“…Desde então, mais 4 eventos similares foram detetados, na verdade, em frequências audíveis para um humano [7][8][9] . Em agosto do presente ano foi anunciada a observação de ondas originadas na fusão de duas estrelas de neutrões, e, simultaneamente, também a observação de radiação gama e no visível 10,11 .…”
Section: Ondas Gravitacionaisunclassified